Genome-wide analysis of multidrug resistant shigella SPP. Isolated from clinical setting in Lebanon. (c2019) - Salem, Yara J. (2019)
Shigella spp. are Gram-negative rod-shaped bacteria belonging to the family Enterobacteriaceae and are known to be a major cause of bacillary dysentery worldwide. In this study, whole-genome sequencing was used for the molecular characterization of ESBL producing Shigella spp. isolates collected from hospitals in Lebanon. PCRs were performed to detect β-lactam resistance gene reservoirs and to identify genes involved in virulence and host adaptation. PCR-based replicon typing (PBRT) was performed to identify patterns of plasmid distribution. For comparative analysis, multi-locus sequence typing (MLST), whole-genome based SNP analysis, Pan-genome analysis and pulsed-field gel electrophoresis (PFGE) were performed to determine the phylogenic relatedness of the isolates and to trace evolutionary lineages. Our study revealed that, eight of the isolates were ESBL producers; resistance to β-lactam was mainly manifested by the presence of blaCTX-M-15, blaCTX-M-3, and blaTEM-1B genes. Inc I1α and IncFII were the prevalent incompatibility groups, with IncI1α being detected in all the isolates, and IncFII in eight of the isolates. β-lactam resistance determinants were found mainly on these two plasmids. class 2 integron was the most common integron detected (nine of the isolates) whereas class 1 was only seen in two of the isolates. The ten sequenced isolates were distributed on three multi-locus sequence types (MLST) (ST152, ST145 and ST245) with ST152 being the predominant. Our study focuses on important virulence determinants and effector proteins used by the bacterium to destroy the host. Individual PCRs were performed to detect the presence of virA (motility), ial (invasion), ipaH (immune system modulation), set and sen (enterotoxins). The study provided an overview of the major plasmid families circulating in multidrug resistant Shigella in Lebanon. The results obtained revealed the role of integrons and gene cassettes in the dissemination of antimicrobial resistant determinants in Shigella and gave an insight of the phylogenic relationships between the undertaken isolates and other worldwide-recovered representatives. This study and through the use of genome-based approaches helped in better understanding the diversity of Shigella, its pathogenesis and drug resistance at the molecular level, and the risk factors associated with the mobilization of plasmids between Shigella spp. and other enteric pathogens